Cybercrime digital crime how technology is utilized for crime - M. Nassir Agustiawan; Arif Budiman; Dian Samudra (IHSA Institute, 2025)
The rapid development of digital technology has brought positive impacts in various aspects of life, such as communication, economy and education. However, on the other hand, this progress also opens up opportunities for various forms of digital crime or cybercrime. Digital crimes include various criminal acts committed through the internet and technology, such as hacking, identity theft, online fraud, malware distribution, and exploitation of personal data. This study aims to understand how technology is utilized to commit crimes in cyberspace, the factors that drive digital criminals, and the implications faced by victims and the wider community. In addition, this study will also discuss strategies and efforts that can be made to prevent and tackle digital crime. With the increasing reliance on technology, it is important for society and legal authorities to be more vigilant and proactive in addressing this challenge. An in-depth understanding of the modus operandi of digital criminals is expected to provide a clearer picture for the development of effective cybersecurity policies